Novel tools to analyse radiation near black holes.
With the current state of scientific knowledge and equipment, understanding astrophysical black holes invariably requires detailed studies of the observable elements surrounding them. The STRONGGRAVITY project has developed novel analytical tools to do just that, with a focus on radiation.
Keywords: Radiation; Black holes